SwissFEL Aramis beamline photon diagnostics. Erratum. (10th May 2019) - Juranić, Pavle; Rehanek, Jens; Arrell, Christopher A.; Pradervand, Claude; Cassar, Ariana; Calvi, Marco; Ischebeck, Rasmus; Erny, Christian; Heimgartner, Peter; Gorgisyan, Ishkhan; Thominet, Vincent; Tiedtke, Kai; et al.
Abstract : The list of authors in the paper byJuranić et al. (2018 ) [ J. Synchrotron Rad. 25, 1238–1248 ] is corrected. Abstract : The list of authors in the paper byJuranić et al. (2018 ) [ J. Synchrotron Rad. 25, 1238–1248] is corrected.